2016
DOI: 10.1002/mpr.1511
|View full text |Cite
|
Sign up to set email alerts
|

Planning to make economic decisions in the future, but choosing impulsively now: are preference reversals related to symptoms of ADHD and depression?

Abstract: A preference for smaller immediate rewards over larger delayed rewards (delay discounting, DD) is common in attention deficit hyperactivity disorder (ADHD), but rarely investigated in depression. Whether this preference is due to sensitivity to reward immediacy or delay aversion remains unclear. To investigate this, we examined whether ADHD and depressive symptoms are associated with preference reversals: a switch from smaller immediate rewards to larger delayed rewards when smaller rewards are also delayed. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
2
4
2
Order By: Relevance
“…When there is no immediate reward option available, but rather the choice is between a sooner (but still delayed) smaller reward and a later (even more delayed) larger reward, people are more likely to wait for larger rewards than if the sooner option were an immediately available reward. However, we found no support for such an exaggerated immediate reward preference in young adults with increased symptom levels of ADHD (Mies, De Water, & Scheres, 2016). Unpublished data from our group, on the other hand, showed that a small group of adolescents with a clinical diagnosis of ADHD did show an increased immediate reward preference compared to controls: When the choice was between receiving $100 after 2 years and a smaller reward (varying in size) after 1 year, the ADHD group was equally willing to wait for the larger amount as the control group was.…”
contrasting
confidence: 89%
See 1 more Smart Citation
“…When there is no immediate reward option available, but rather the choice is between a sooner (but still delayed) smaller reward and a later (even more delayed) larger reward, people are more likely to wait for larger rewards than if the sooner option were an immediately available reward. However, we found no support for such an exaggerated immediate reward preference in young adults with increased symptom levels of ADHD (Mies, De Water, & Scheres, 2016). Unpublished data from our group, on the other hand, showed that a small group of adolescents with a clinical diagnosis of ADHD did show an increased immediate reward preference compared to controls: When the choice was between receiving $100 after 2 years and a smaller reward (varying in size) after 1 year, the ADHD group was equally willing to wait for the larger amount as the control group was.…”
contrasting
confidence: 89%
“…In contrast to the experiential design as applied in our study, previous loss discounting studies have used hypothetical designs (i.e., losses and delays are not actually experienced), in which participants were asked the opposite from what we asked, namely to choose between a smaller immediate loss (e.g., pay 10 dollars now) and a larger delayed loss (e.g., pay 100 dollars after 1 year). These studies have shown that people are inclined to choose larger delayed losses, that is, they discount losses (Estle, Green, Myerson, & Holt, 2006;Mies et al, 2016;Tanaka, Yamada, Yoneda, & Ohtake, 2014;Thaler, 1981). It should be noted, though, that losses are generally discounted less steeply than gains, which is known as the sign effect (e.g., Estle et al, 2006).…”
mentioning
confidence: 99%
“…Thus, this finding could be taken as an indication that delay-related behaviors are a transdiagnostic feature that is related to several different types of mental health problems. In line with this interpretation, previous studies have found that delay-related behaviors are not only associated with ADHD symptom levels, but also with anxiety and depression (Clare et al, 2010;Mies, De Water, & Scheres, 2016).…”
Section: Neuropsychological Deficits Daily Life Functioning and Quasupporting
confidence: 56%
“…Significant, although somewhat weaker, relations were also found between QDQ scores and symptoms of both anxiety and depression. Significant relations between the QDQ scores and both ratings of ADHD symptoms and depression have also been confirmed in a more recent study (Mies, de Water, & Scheres, 2016). The study by Mies and colleagues also found evidence for convergent validity of the QDQ because high scores on the two QDQ subscales were associated with a higher number of choices for smaller sooner rewards compared with larger later rewards in a delay-discounting task using hypothetical rewards.…”
mentioning
confidence: 65%
“…We only found weak, nonsignificant, associations between QDQ scores and scores from a laboratory measure of delay discounting. To our knowledge, only one previous study (Mies et al, 2016) has studied this relation. This study did find significant relations to the two QDQ subscales, but the size of the effect was very small.…”
Section: Relations Between Scores On the Qdq And The Delay-discountin...mentioning
confidence: 99%